PENGARUH TERPAAN INFORMASI PROBLEM LAYANAN INDIHOME TERHADAP SENTIMEN OPINI PUBLIK (STUDI EKSPLANATIF KHALAYAK DALAM MENANGGAPI LAYANAN INDIHOME) - Annisa Lastania Ayuning Pramesti, (2023)
This research is motivated by the disruption of Indihome services as the biggest Internet Service Provider in Indonesia. The disturbances that occurred have generated several unfavorable opinions and attitudes from the public as seen from the hashtag #Indihomedown which is trending on social media and various news exposures in the mass media regarding service disruptions. The need for internet services during the Covid-19 pandemic has highlighted how important access to internet services and digital technology is for all people, regardless of economic, political, social or geographical conditions. Customers fixed broadband in Indonesia most use the IndiHome service owned by PT Telkom Indonesia and make Indihome certainly the community's foundation for their internet needs. Good Internet service is a basic need for the community to carry out their activities online. This study intends to explain the relationship between the influence of information exposure on Indihome service problems on public opinion sentiment. The theory used in this study is Uses and Effect, this theory explains the relationship between mass communication conveyed through the mass media can create an effect (effects) for mass media users. The purpose of this study is to prove and analyze how information exposure related to Indihome service problems can influence the formation of public opinion and have an effect on service users. The research method used in this study is using explanatory research with a quantitative approach. Data collection was carried out by distributing questionnaires to 106 respondents who were Indihome users and received exposure to information about Indihome service problems. The results showed that there was a simultaneous effect of 15.8% between information exposure to Indihome service problems on public opinion sentiment. The hypothesis test in this study showed that H0 was rejected, and Ha was accepted. It can be concluded that the variable Exposure to Indihome Service Problem Information (X) has a significant effect on Public Opinion (Y). Keywords: information exposure, service problems, covid-19, public opinion